A Model of Climate Policy Using Board Game Mechanics - Edward Castronova; Isaac Knowles (Serious Games Society, 2015)
This paper provides a case study of how a board game can be modified to generate a serious game. We argue that board games are an interesting medium for serious games, especially when the goal is to teach players about particularly complex systems. In that case, the transparency of a board game makes it possible for players to "see the whole boards" - to see all of the various moving parts at work. That transparency also makes it very easy to modify board games. To demonstrate these claims, we present a modification to the board game CO2 that accurately models different policy options with regard to global warming. We show how a few major changes to the original game's point systems, as well as removal of certain extraneous features, can significantly improve the game, adding an instructional value. The game allows players to experiment with several policy options, including carbon taxes, carbon emissions permit sales, and clean energy research support, and lets players see how these policies interact. We discuss ways that teachers, advocates, journalists, and others can the Climate Policy mod to more easily explain the incredibly complex interactions of power markets, carbon dioxide emissions, and public policy.